The Urgency of Revitalizing the Organization of the Directorate General of Taxes (DJP) into a State Revenue Agency (BPN) from a Constitutional Law Perspective - Fatmawati Fatmawati; Febrian Febrian; Ridwan Ridwan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
The institutional position of the Directorate General of Taxes (DJP) under the Ministry of Finance has raised concerns regarding its organizational autonomy in managing taxation policies, human resources, budgeting, and information technology. This study aims to analyze the constitutional urgency of revitalizing the DJP into an independent State Revenue Agency (Badan Penerimaan Negara/BPN) that is directly accountable to the President. The research employed a normative juridical approach using a descriptive-analytical method by examining constitutional provisions, statutory regulations, legal doctrines, and relevant literature related to taxation governance and institutional reform. The analysis indicates that the current institutional arrangement limits the DJP's operational independence and may reduce the effectiveness of tax administration. Comparative experiences from several countries also demonstrate that autonomous revenue authorities tend to achieve greater efficiency, accountability, and tax collection performance. From the perspective of Indonesian constitutional law, the establishment of an independent State Revenue Agency does not conflict with the 1945 Constitution, provided that it is established through an appropriate legal framework and remains subject to constitutional principles, checks and balances, and public accountability. Therefore, revitalizing the DJP into a State Revenue Agency constitutes a strategic institutional reform to strengthen tax administration, improve state revenue performance, and promote good governance in Indonesia.